Search Title: - Drafting formation in pop art and their reflection in the artistic productions for students of art education (Journal of the College of Basic Education, 2022)
The wording formation in pop art was driven metaphors for the Perception shapes and images according to adopt employment inspirational and emotional and popular social realist and gustatory elements construction intellectual Cloth therefore determine the title to the character ((composition formulation in pop art and their reflection in the artistic productions for students of art education)) Derive the importance of research to highlight the formulation composition in the pop art and the extent reflected in the products of art education students, as established ideas in the concepts of the aesthetics of composition of the technical achievements of the visual and the vision of the contemporary visual scene. It was the aim of the research disclosure of the formulation composition and mechanism of functioning of the raw material in the pop art, and Titan the reflection of pop art in artistic productions for students of education Alphenah.ama theoretical framework guarantees the review of the emergence of pop art and its features and characteristics of the most important techniques with models of the products of the most prominent artists. Feat field researcher analytical study was to determine the product of 80 students of the Department of Art Education at the Faculty of Fine Arts - University of Baghdad, a society for research, were analyzed 12 of them as a sample product, Was preparing a special form of analysis it has been agreed upon after a presentation to a group of experts. One of the most important outcomes of the research inspired the formulation composition Folk Art in most of the products of the students, where they found the researcher that the reflection of the possibility of employing article by the multiplicity of raw materials used in structural work of art and techniques of installation of treatment was clear and a reflection of what in pop art. As Zaraadm use some of the techniques and methods for this kind of art, including the exploitation of marginalized environmental waste and the main points of pop art. as the most important conclusions was to speak freely wide by students to express what wanders in their minds without any identification of the type or style of work or comply with certain variations which allowed Giralmalov and show them Alaptaaden realism and other styles Alkadimh.oagira list of sources, references and appendices.